'Melting Worlds' and 'Climate Myths': Diverging Stories of Climate Change in Longyearbyen, an Arctic 'Frontline Community' - Meyer, Alexandra (Ethnos, 2024)
Abstract Climate change is a powerful story in Longyearbyen, the largest settlement on Svalbard in the high Arctic. While most natural science agrees on accelerating climate change with profound environmental impacts, this article unpacks the multidimensionality of the topic locally. By approaching climate change as a discourse, we explore the reception and reproduction of the dominant climate change discourse locally and compare it to other stories about climate change and adaptation. With this, we aim to contribute to the growing field of reception studies in anthropology. Our data, gathered through ethnographic fieldwork including interviews and informal conversations, include counterstories that nuance and contest the dominant climate change discourse. They point to over-simplification, sensationalism and the (mis)use of the climate discourse for other purposes. Such counterstories must be listened to in order to move in the direction of fair, inclusive, and transparent climate change politics.